Impact of Ammonium on Syntrophic Organohalide-Respiring and Fermenting Microbial Communities - Delgado, A. G.; Fajardo-Williams, D.; Kegerreis, K. L.; Parameswaran, Prathap; Krajmalnik-Brown, R. (My University, 2016)
Syntrophic interactions between organohalide-respiring and fermentative microorganisms are critical for effective bioremediation of halogenated compounds. This work investigated the effect of ammonium concentration (up to 4 g liter(-1) NH4+-N) on trichloroethene-reducing Dehalococcoides mccartyi and Geobacteraceae in microbial communities fed lactate and methanol. We found that production of ethene by D. mccartyi occurred in mineral medium containing <= 2 g liter(-1) NH4+-N and in landfill leachate. For the partial reduction of trichloroethene (TCE) to cis-dichloroethene (cis-DCE) at >= 1 g liter(-1) NH4+-N, organohalide-respiring dynamics shifted from D. mccartyi and Geobacteraceae to mainly D. mccartyi. An increasing concentration of ammonium was coupled to lower metabolic rates, longer lag times, and lower gene abundances for all microbial processes studied. The methanol fermentation pathway to acetate and H-2 was conserved, regardless of the ammonium concentration provided. However, lactate fermentation shifted from propionic to acetogenic at concentrations of >= 2 g liter(-1) NH4+-N. Our study findings strongly support a tolerance of D. mccartyi to high ammonium concentrations, highlighting the feasibility of organohalide respiration in ammonium-contaminated subsurface environments. IMPORTANCE Contamination with ammonium and chlorinated solvents has been reported in numerous subsurface environments, and these chemicals bring significant challenges for in situ bioremediation. Dehalococcoides mccartyi is able to reduce the chlorinated solvent trichloroethene to the nontoxic end product ethene. Fermentative bacteria are of central importance for organohalide respiration and bioremediation to provide D. mccartyi with H2, their electron donor, acetate, their carbon source, and other micronutrients. In this study, we found that high concentrations of ammonium negatively correlated with rates of trichloroethene reductive dehalogenation and fermentation. However, detoxification of trichloroethene to nontoxic ethene occurred even at ammonium concentrations typical of those found in animal waste (up to >= 2 g liter(-1) NH4+-N). To date, hundreds of subsurface environments have been bioremediated through the unique metabolic capability of D. mccartyi. These findings extend our knowledge of D. mccartyi and provide insight for bioremediation of sites contaminated with chlorinated solvents and ammonium.
Citation: Delgado, A. G., Fajardo-Williams, D., Kegerreis, K. L., Parameswaran, P., & Krajmalnik-Brown, R. (2016). Impact of Ammonium on Syntrophic Organohalide-Respiring and Fermenting Microbial Communities. Msphere, 1(2), 10. doi:10.1128/mSphere.00053-16
Keywords: Dehalococcoides Mccartyi; Geobacter; Ammonia; Fermentation; Organohalide; Respiration